A SWCNT based aptasensor system for antibiotic oxytetracycline detection in water samples. Issue 20 (13th May 2019) - Yildirim-Tirgil, Nimet; Lee, Jinyoung; Cho, Hanchul; Lee, HeaYeon; Somu, Sivasubramanian; Busnaina, Ahmed; Gu, April Z.
Abstract : A simple and highly sensitive aptamer-based single walled carbon nanotubes (SWCNTs) biosensor for fast and specific oxytetracycline detection in environmental water samples. Abstract : Oxytetracycline (OTC) is a member of the broad-spectrum tetracycline (TC) group of antibiotics and TCs are widely used to prevent bacterial infections in livestock and increase their growth rate. Hence a large percentage of the antibiotics is either accumulated in tissues or excreted and released into the environment that leads to serious health implications such as antibiotic resistance. Thus, simple, fast and easy to use methods are needed for OTC detection. Here a simple and highly sensitive aptamer-based single walled carbon nanotube (SWCNT) biosensor containing probe-DNA immobilized on functionalized SWCNTs was developed for fast and specific OTC detection. We employed a newly developed flexible biosensor device which was fabricated by a high-rate nanoscale offset printing process using directed assembly and transfer of SWCNTs. Employing a simple directed assembly and non-covalent functionalization process these fabricated probe DNA-based SWCNT biosensors were designed with two electrode terminals to allow continuous resistance response monitoring for antibiotics detection. The developed environmental sensor had a detection range of 10 μg L −1 to 75 μg L −1 (20–325 nM), with a detection limit of 1.125 μg L −1 (2.5 nM). When compared to other biosensors such as colorimetric, electrical or cantilever-based biosensor systems, the biosensor developed here is simpler and faster (less than 10 minutes, including pre-incubation, measurement and regeneration) with a lower detection limit. And the portable platform also allows for potential on-site or real-time measurements. The biosensor could be regenerated and reused over 20 times with good stability with signal decrease less than 15%. In addition, its inherent miniature size makes this biosensor potentially useful for a simple portable model for environmental and industrial applications.